A Comparative Study on the High-Temperature Forming and Constitutive Modeling of Ti-6Al-4V - Uz, Murat Mert; Yoruc, Afife Binnaz Hazar; Aydogan, Cahit Sertac; Yapici, Guney Guven (SPRINGER, 2023)
Ti-6Al-4V alloy is often preferred for high-performance components such as aerospace components due to its superior material properties and thermal resistance. In order to produce these components in the desired geometry, it is very important to determine the high-temperature thermomechanical properties of Ti-6Al-4V. In order to define these properties, uniaxial tensile tests at strain rates of 0.001, 0.01 and 0.1 s(-1) at 700, 750 and 800 degrees C were applied in this study. In tests performed at a strain rate of 0.001 s(-1) at 800 degrees C, an elongation at break above 0.8 representing a dominant ductile behavior is observed. It is clearly demonstrated that the initial 17.32% beta phase reaches 31.02% at 800 degrees C, and the alpha grain size increases with temperature. Existence of dimples and voids in the fracture surfaces are an indicator of increased ductility behavior. In addition to the Modified Johnson-Cook model, which is widely used for modeling flow stress, the use of the extended Ludwik equation is suggested in this study. According to the correlation coefficient (R), it is claimed that the Extended Ludwik model is a more suitable approach for modeling the mechanical behavior for the studied forming temperature range.
Keywords: constitutive modeling; hot forming; material characterization; Ti-6Al-4V alloy; MODIFIED ZERILLI-ARMSTRONG; HOT DEFORMATION-BEHAVIOR; MODIFIED JOHNSON-COOK; STRAIN-RATE; FRACTURE CHARACTERISTICS; TITANIUM-ALLOY; FLOW BEHAVIOR; MICROSTRUCTURE; EQUATION; PREDICT; Materials Science